2017
DOI: 10.1103/physrevlett.119.023603
|View full text |Cite
|
Sign up to set email alerts
|

Topological Quantum Optics in Two-Dimensional Atomic Arrays

Abstract: We demonstrate that two-dimensional atomic emitter arrays with subwavelength spacing constitute topologically protected quantum optical systems where the photon propagation is robust against large imperfections while losses associated with free space emission are strongly suppressed. Breaking timereversal symmetry with a magnetic field results in gapped photonic bands with nontrivial Chern numbers and topologically protected, long-lived edge states. Due to the inherent nonlinearity of constituent emitters, suc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
187
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(197 citation statements)
references
References 70 publications
5
187
0
Order By: Relevance
“…As was shown in [74] and also observed in [75], all states that lie outside the circle |k| = κ are subradiant, i.e., they decay with a rate much smaller than the single atom decay rate . Hence, remarkably, we find that while in case (i) the dissipation makes the excitation decay after only a few sites, the excitation in case (ii) is much less affected by the dissipation (see discussion in [57]).…”
supporting
confidence: 65%
See 1 more Smart Citation
“…As was shown in [74] and also observed in [75], all states that lie outside the circle |k| = κ are subradiant, i.e., they decay with a rate much smaller than the single atom decay rate . Hence, remarkably, we find that while in case (i) the dissipation makes the excitation decay after only a few sites, the excitation in case (ii) is much less affected by the dissipation (see discussion in [57]).…”
supporting
confidence: 65%
“…We have shown that one can excite edge states that allow for the transport of an excitation over long distances along the edge of the lattice that are robust to the presence of defects. Moreover, these edge states are remarkably long-lived due to the collective character of the dissipation (this effect has also been investigated in [74,75]). Finally, we have found that, due to the long-ranged character of the interactions, the bulk-boundary relations, well established for topological insulators with short-range interactions, are not generally valid in our setting.…”
mentioning
confidence: 95%
“…Quantum optical properties of lattices of atoms and atomlike emitters are being actively explored both theoretically and experimentally [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. In such lattices, atoms are assumed to be confined such that tunneling between sites is negligible and they interact via photon-mediated dipole-dipole interactions giving rise to hybridized atom-photon bands.…”
Section: Introductionmentioning
confidence: 99%
“…The photonic band structure of three-dimensional (3D) atomic lattices has been investigated in a number of studies [2][3][4][5][6]. Recently, there has been significant interest in the photonic properties of two-dimensional (2D) atomic lattices, which have been shown to exhibit a variety of remarkable phenomena, including subradiance [15][16][17][18], near perfect reflection of radiation [12,14], and long-lived topological excitations [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…From the experimental side, recent proposals with Shiba states [31][32][33][34], Floquet Hamiltonians [35,36], atoms coupled to radiation fields [37][38][39], and trapped ions [40] opened the possibility to synthesize and observe the mentioned LR physics.…”
mentioning
confidence: 99%